Yield losses caused by the sugarcane mosaic virus in plots with different levels of infection in the sets. I. Losses in plant-cane - Matsuoka, Sizuo; Costa, Álvaro S. (Pesquisa Agropecuaria Brasileira, 2014)
Experiments to determine the yield losses induced by the sugarcane mosaic virus were carried out in Sertãozinho and Lençóis Paulista, São Paulo. The plots were planted with four levels of initial mosaic infection, e.g., 0, 25, 50 and 100%. Virus spread in the experimental plots of the variety CB 46/47 was noticeable, but it was negligible for the variety IAC 50/134. The linear regression of plant-cane yield on increased mosaic infection was significant for the two varieties and two localities. Yield differences between initially healthy and 25% mosaic infected plots were significant for CB 46/47; percentages of yield reductions were 27 and 19%, in Sertãozinho and in Lençóis Paulista, respectively. In the 100% infected plots, the yield reduction was 71%, in the two localities. For the variety IAC 50/134 the only highly significant difference in yield was between plots planted with healthy sets and plots planted with 100% infected sets; percentage wise, the yield difference was 18%, in the two localities. Juice analyses of healthy and diseased canes revealed no differences.